A Dual Protection System for Heterostructured 3D CNT/CoSe2/C as High Areal Capacity Anode for Sodium Storage. Issue 5 (21st January 2020) - Yousaf, Muhammad; Chen, Yijun; Tabassum, Hassina; Wang, Zhipeng; Wang, Yunsong; Abid, Adeel Y.; Mahmood, Asif; Mahmood, Nasir; Guo, Shaojun; Han, Ray P. S.; Gao, Peng
Abstract: 3D electrode design is normally opted for multiple advantages, however, instability/detachment of active material causes the pulverization and degradation of the structure, and ultimately poor cyclic stability. Here, a dually protected, highly compressible, and freestanding anode is presented for sodium‐ion batteries, where 3D carbon nanotube (CNT) sponge is decorated with homogeneously dispersed CoSe2 nanoparticles (NPs) which are protected under carbon overcoat (CNT/CoSe2 /C). The 3D CNT sponge delivers enough space for high mass loading while providing high mechanical strength and faster conduction pathway among the NPs. The outer amorphous carbon overcoat controls the formation of solid electrolyte interphase film by avoiding direct contact of CoSe2 with electrolyte, accommodates large volume changes, and ultimately enhances the overall conductivity of cell and assists in transmitting electron to an external circuit. Moreover, the hybrid can be densified up to 11‐fold without affecting its microstructure that results in ultrahigh areal mass loading of 17.4 mg cm −2 and an areal capacity of 7.03 mAh cm −2 along with a high gravimetric capacity of 531 mAh g −1 at 100 mA g −1 . Thus, compact and smart devices can be realized by this new electrode design for heavy‐duty commercial applications. Abstract : A 3D and dually protected electrode design (carbon nanotube (CNT)/CoSe2 /C) is presented in which a CNT sponge is decorated with CoSe2 nanoparticles and then externally protected with carbon layers. The representative 3D CNT/CoSe2 /C heterostructure has the ability to be densified without influencing its microstructure that results in high areal capacity along with high gravimetric capacity for sodium‐ion batteries.